Performance analysis of cloud-based cve communication architecture in comparison with the traditional client server, p2p and hybrid models - Gital, Abdulsam Ya'u; Abdul Samad, Ismail; Haruna, Chiroma; Abubakar, Adamu; Bala Ma’aji, Abdulhamid; Maitama, Jaafar Zubairu; Zeki, Akram M. (2014)
Gital et al. (2014) proposed a cloud based communication architecture for improving efficiency of collaborative virtual environment (CVE) systems in terms of Scalability and Consistency requirements. This paper evaluates the performance of the proposed CVE architecture. The metrics use for the evaluation is response time. We compare the cloud-based architecture to the traditional client server and peer-2–peer (P2P) architecture. The comparison was implemented in the CVE systems. The comparative simulation analysis of the results suggested that the CVE architecture based on cloud computing can significantly improve the performance of the CVE systems